Literasi Keuangan Pelaku Usaha Kecil di Kecamatan Bajawa Kabupaten Ngada - Yolanta Alina Loda Siu; Gabriel Tanusi (FAKULTAS EKONOMI UNIVERSITAS FLORES, 2020)
Understanding and knowledge in managing finances (financial literacy) are needed by small entrepreneurs in Bajawa District. This study aims to analyze the influence of gender, income, investment, saving and borrowing, and insurance on financial literacy in small businesses in Bajawa District. The research method used is a survey method by obtaining data through questionnaires and interviews, with a total sample of 119 business actors. The data analysis technique used multiple linear regression analysis. The results showed that the level of financial literacy of Small Entrepreneurs in Bajawa District was in the Low category (56.50%). Variables gender, income, investment, saving and borrowing, insurance partially or simultaneously have an effect on the level of financial literacy of small entrepreneurs in Bajawa sub-district.